Proceso de atención de enfermería en la taquipnea transitoria del recién nacido en neonato de sexo femenino de dos horas de vida extrauterina - Castellano Gomez, Yeraldine (2018)
Transient tachypnea of the newborn or also called wet lung is a benign process that involves the persistence of liquid surfactant in the lungs of the newborn after delivery. The pulmonary epithelium of the RN that during the pregnancy is a CL secreting active and liquid towards the alveoli, has to become an active and absorber of NA and liquid. With the objective of removing the latter, which is conditioned by the presence of catecholamines secretaries during labor that stimulate so-called NA channels. When a labor does not occur, distension of the interstitial spaces takes place due to the pulmonary fluid that leads to the entrapment of the alveolar air and to the decrease of the pulmonary distensibility. Multiple factors can give rise to its etiology such as: cesarean delivery, diabetic mother, prematurity, male sex, vaginal delivery and macrosomia. Among the main symptoms we have: tachypnea, vesicular murmur, oxygen requirement, nasal flapping and xiphoid retraction. In the treatment of transient tachypnea of the newborn it is based on the administration of oxygen according to the need of the neonate. In several occasions the administration of antibiotics is also required to prevent the risk of possible infections. Among the possible complications that may occur in cases of transient tachypnea of the newborn we have: cerebral hemorrhage, infection, air leakage and anemia